THE MITIGATION STEERING BIAS CURVES FOR INDUSTRIAL TRANSPORT - Korzhenevych, I. P.; Gots, O. V. (Science and Transport Progress, 2007)
Influencing of decline of coefficient of rolling friction is examined in curves on the size of softening of leadingslope.